Optimizing number of cycles of induction chemotherapy for patients with nasopharyngeal carcinoma: Retrospective survival analysis. Issue 8 (23rd March 2020) - He, Yan; Zhao, Zhihao; Wang, Ying; Chai, Jiamin; He, Jialing; Wang, Jingjing; He, Ling; Guan, Hui; Wei, Zhigong; Liu, Zheran; Mu, Xiaoli; Peng, Xingchen
Abstract: Background: Induction chemotherapy followed by concurrent chemoradiotherapy is one of the standards of care for patients with nasopharyngeal carcinoma, but the optimal number of induction cycles is unclear. Here we compared survival data from patients treated with 2 to 4 cycles. Methods: Patients with nasopharyngeal carcinoma at West China Hospital of Sichuan University between January 2009 and December 2015 were retrospectively analyzed. Results: Six hundred and seventy three patients met eligibility criteria. After a median follow‐up of 53 months (interquartile range, 38‐74), there was no difference between 2 and 3 cycles in overall survival (88.14% vs 91.24%). But four cycles were associated with worse overall survival (79.12%) and higher incidence of treatment‐related toxicities. Multivariate analysis showed that the number of induction cycles and lymph node classification were prognostic factors. Conclusions: Two and three cycles of induction chemotherapy are associated with similar survival, while four cycles reduce survival and increase treatment‐related toxicity in endemic regions.